3(v+6)=-3(6v-7)+6v

Simple and best practice solution for 3(v+6)=-3(6v-7)+6v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(v+6)=-3(6v-7)+6v equation:


Simplifying
3(v + 6) = -3(6v + -7) + 6v

Reorder the terms:
3(6 + v) = -3(6v + -7) + 6v
(6 * 3 + v * 3) = -3(6v + -7) + 6v
(18 + 3v) = -3(6v + -7) + 6v

Reorder the terms:
18 + 3v = -3(-7 + 6v) + 6v
18 + 3v = (-7 * -3 + 6v * -3) + 6v
18 + 3v = (21 + -18v) + 6v

Combine like terms: -18v + 6v = -12v
18 + 3v = 21 + -12v

Solving
18 + 3v = 21 + -12v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '12v' to each side of the equation.
18 + 3v + 12v = 21 + -12v + 12v

Combine like terms: 3v + 12v = 15v
18 + 15v = 21 + -12v + 12v

Combine like terms: -12v + 12v = 0
18 + 15v = 21 + 0
18 + 15v = 21

Add '-18' to each side of the equation.
18 + -18 + 15v = 21 + -18

Combine like terms: 18 + -18 = 0
0 + 15v = 21 + -18
15v = 21 + -18

Combine like terms: 21 + -18 = 3
15v = 3

Divide each side by '15'.
v = 0.2

Simplifying
v = 0.2

See similar equations:

| 6x-8+5=13x-4+9 | | 24+.16n=40 | | -11v-10v+14v-14v=14 | | 7n-13=13n-15 | | 2Ln(x)+Ln(x-1)=Ln(-2x^2+5x-3) | | -4w-4(5x-5w)+3x= | | X^2-32x+225=0 | | y=50x+1.50 | | 2u-2+2(4u+2)=-2(u+6) | | 15x+-11x+-7x=18 | | 3r-18=2r-12 | | -3a-1=7a | | 6timesd+136=400 | | 1ab+2bc-7ac=10 | | -2x+34=x+16 | | -3(t+5)=-36 | | 12(23x+46y)+23=762 | | 5t^2-13t-2=0 | | 20x/24 | | x^3+25x-3=0 | | -x-29=4x+11 | | 17t-3t+8t+17t=-11 | | 36+x=4(6+x) | | 1a+2b+3c=4d | | 4a+6=2a-10 | | 3(2+5)=15 | | 1x+2y=3x | | -1=3r+22 | | 115x+935x=1 | | 16p-15p+3p-3p=15 | | -10(s+4)=-73 | | 115x+935x=9000 |

Equations solver categories